Out of the dark void: Ommatoiulus longicornis n. sp., a new julid from Spain (Diplopoda, Julida) with notes on some troglobiomorphic traits in millipedes - Akkari, Nesrine; Gilgado, José D.; Ortuño, Vicente M.; Enghoff, Henrik (Zootaxa, 2018)
A new millipede species, Ommatoiulus longicornis n. sp. is described from the subterranean habitat in eastern Spain, and the elongation of its antennae is discussed in relation to the habitat where it dwells. We take the occasion to discuss the elongation of appendages as a troglobiomorphic character in millipedes and shed the light on the various, sometimes controversial, hypotheses that could have led to these modifications in millipedes and other subterranean arthropods.